Learning Styles in Learning English - Putra M, M Rafly Dwi (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to find out What kinds of student learning styles in Learning English and what learning styles are most commonly used by students in learning English. This study uses quantitative research methods, non-probability sampling techniques with total sampling techniques. The sample in this study was 47 respondents. The results showed that the learning styles that generally exist in English learning are visual learning, auditory learning, and kinesthetic learning. The learning style that is most widely used in general is the visual learning style.